Implementasi Strategi Promotional Mix untuk Meningkatkan Pelanggan Pada Minimarket/ Swalayan di Kota Tegal - Makmur Sujarwo; Sumarno Sumarno; Tabrani Tabrani (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
This research aims to find out how far promotional mix strategies such as advertising, personal selling and sales promotion variables have been implemented in minimarkets / supermarkets in Tegal City so as to increase the number of customers. The sample used in this study was 231 respondents as customers spread across several minimarkets / supermarkets in Tegal City. Respondents answered questionnaire questions distributed at minimarkets / supermarkets in Tegal City. Respondents answered closed-door questions that were then processed using multiple regression tests with IBM SPSS Statitistic 22 analysis tool. The results showed that all the variables in this study such as sales promotion, advertising and personal selling had a positive and significant influence on the increase in the number of customers in minimarkets / supermarkets in Tegal City. Should minimarkets / supermarkets in Tegal City in order to increase more vociferous promotions such as providing attractive discounts, giving gifts, high advertising intensity and approaching customers who are troubled in finding certain products and handling their complaints well.